Implications of the Syrian Civil War on the Alawites - Bayram Sinkaya (İnsan & Toplum)
Anti-regime demonstrations erupted in Syria in 2011 that turned into armed conicts and then a civil war wrecked the country for over eight years have profoundly impacted all social groups. !e Alawite background of the long-lasting ruling family, the Assads, and the growing sectarian characteristics of the conict drew projections particularly on the Alawite community. Indeed, it was regarded very critical both for the continuation of the ruling regime, and for the potential success of its opposition. !ere have been many debates in various occasions on the Alawite’s relations with the opposition and the Assad administration, however, currently there are few scholarly researches on implications of the civil war with regard to the Alawite community. Moreover, the existing literature underexplored communitarian concerns of the Alawites and effects of clashes on them. It also underestimated breaks among the Alawites, and their complicated relations with the regime and the opposition. !is article aimed at analyzing the position of Syrian Alawites in a period that start with the anti-government demonstrations that evolved into the civil war. In this respect, it reviewed the Alawites’ relations with both the Assad administration and the opposition, and it discussed implications of the civil war on this community. It appeared that the Alawites did not act in a monolithic way in the face of anti-regime demonstrations; while some of them stood behind the Assad administration, a considerable part of them tended towards opposition. However, the growing sectarian color of the conict that deepened sectarian concerns of the most of the Alawites, led them to extend their support to the Assad administration against the Islamist-dominated opposition. However, it did not mean that the Alawites had seamless relations with the Assad administration; and the Alawite support for the Assad could not be explained solely by sectarian reasons. !ere has been a number of sociological, historical and political factors that affected the Alawite choice.